Aktivitas Hipoglisemik Ekstrak Herba Sambiloto (Andrographis paniculata Nees, Acanthaceae) - Soediro Soetarno; Elin Yulinah Sukandar; Sukrasno Sukrasno; Agung Yuwono (Jurnal Matematika & Sains, 1999)
Hypoglycemic activity of hexane, ethylacetate, ethanol and aqueous extract of Andrographis paniculata herbs had been tested using glucose tolerance test. Extraction was conducted consecutively using hexane, ethylacetate and ethanol. Aqueous extract was obtained directly from the crude drug similar to the traditional use. At the dose level of 0.5 g/kg bw, hexane and ethylacetate extract did not show the hypoglycemic effect. Significant activity was shown by ethanol and aqueous extract and the activity of the latter was higher than the former.